Effect of Doping Agent on Elution Profile of Tc-99m Generationand Labeling of Tc-99m With (Journal of Chemical Engineering, 2014)
Effect of doping agent on elution profile of Tc-99m generation and labeling of Tc-99m with MDP (Methylene diphosphonate) were carried out and studied. Tc -99m is one of the most talked element of modern radio pharmacy for its multiple application in diagnosis.Tc-99m is produced from Mo-99 through radioactive decay process. In our work two column chromatographic generator were made with Alumina column and loaded with Mo-99 which would be converted into Tc-99m eventually. Elution was taken by passing saline( 1 mL 0.9% NaCl solution and 1 mL 0.9% NaCl solution with 0.0045% NaNO3 as doping agent) each time and the activities of Tc -99m was measured by a Dose Calibrator. Elutions of Tc-99m were carried out several times and each time activity was measured. It is observed that almost 60 -75 % activity can be found in 2nd elution. Studying elution profile it is seen that activity curve reaches at pick in 2nd elution and afterwards gradually slopes down. Each time better activity is achieved by using pure saline. In spite of lower activity, this research resulting highly recommendation of using NaNO3 as a doping agent in NaCl saline in case of using elution because of its higher purity and RCP value . Tc -99m is applied over a biological body as a labeled compound . In this case MDP was used as a labeling compound . With a view of carrying out the RCP value of labeled compound, paper chromatography technique is done with various mobile phases in Whatman No 1 paper. Purity (%) is ranging from 30 90 % and NaNO3 doped NaCl radioactive solution shows better purity performance than pure NaCl solution in every different mobile phase . DOI: http://dx.doi.org/10.3329/jce.v27i2.17800 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 41-45